An Exhaustive Survey on Authentication Classes in the IoT Environments - Dargaoui, Souhayla; Azrour, Mourade; El Allaoui, Ahmad; Guezzaz, Azidine; Alabdulatif, Abdulatif; Alnajim, Abdullah (IAES Indonesian Section, 2024)
In today's world, devices are interconnected across various fields, ranging from intelligent buildings and smart cities to Industry 4.0 and smart healthcare. IoT security is still the biggest obstacle to deployment despite the exponential growth of IoT usage in our world. The principal objective of IoT security is to warrant the accessibility of services offered by an IoT environment, protect privacy, and confidentiality, and ensure the safety of IoT users, infrastructures, data, and devices. Authentication has become a top priority for everyone because it is the first line of defense against security threats and can allow or prevent users from accessing resources according to their legitimacy. Consequently, studying and researching authentication issues within IoT is extremely important. Our paper provides a comparative study of current IoT security research; it analyzes recent authentication protocols from 2018 to 2024. This survey’s goal is to provide an IoT security research summary, the biggest susceptibilities, and attacks, the appropriate technologies, and the most used simulators.